2011
DOI: 10.1177/0020764010390433
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of anxiety and depressive disorders: A comparative population study in Western and non-Western inhabitants in the Netherlands

Abstract: The high prevalence rate of comorbid anxiety and depressive diorders in non-Western immigrants in the Netherlands necessitates assesssment and treatment of both disorders. There was no indication of a - culturally influenced - stronger overlap between anxiety and depressive disorders in non-Western immigrants in the Netherlands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…[27][28][29][30] Also, cultural and social differences between ethnic groups (eg, language barriers, unfamiliarity with the obstetric care organisation) may explain differences between ethnic groups regarding the influence of anxiety on the birth process. [31][32][33][34] In addition, it is unknown whether the association between anxiety and the birth process differs between nulliparous and multiparous women as well as between women giving birth in primary and secondary care. To our knowledge, no study has investigated the level of care and ethnicity in the association between general and pregnancy-related anxiety, and the progression of birth.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30] Also, cultural and social differences between ethnic groups (eg, language barriers, unfamiliarity with the obstetric care organisation) may explain differences between ethnic groups regarding the influence of anxiety on the birth process. [31][32][33][34] In addition, it is unknown whether the association between anxiety and the birth process differs between nulliparous and multiparous women as well as between women giving birth in primary and secondary care. To our knowledge, no study has investigated the level of care and ethnicity in the association between general and pregnancy-related anxiety, and the progression of birth.…”
Section: Introductionmentioning
confidence: 99%
“…Mean scores differed significantly between ethnic groups. Depression (assessed either by CIDI or SCL-90-R) was equally associated with functional impairment across ethnic groups, since the interaction terms with ethnicity were not significant 16 .…”
Section: E) Association Of Depression and Functional Impairmentsmentioning
confidence: 91%
“…The odds ratio of anxiety for depressive severity in Dutch natives is 2.6 (95% CI: 1.6-4.2). Compared to native Dutch subjects as reference group (OR set to 1), the unadjusted odds ratio of the presence of an anxiety disorders for depressive disorder severity was 1.1 (p = 0.849) in Turkish-Dutch and 1.6 (p = 0.221) in Moroccan-Dutch subjects 16 .…”
Section: B) Co-morbidity Of Anxiety Disorders and Depressive Disordersmentioning
confidence: 93%
See 1 more Smart Citation
“…When looking more specifically at the Netherlands, previous studies found that individuals of Turkish and Moroccan origin have a poorer self-perceived health (Stronks et al 2001) and report more physical and psychological health problems, more missed days due to health problems, and more long-term health limitations (Reijneveld 1998). Moreover, individuals of Turkish and Moroccan backgrounds have a higher prevalence of depressive symptoms (de Wit et al 2008;Ikram et al 2014;Klaufus et al 2014;Levecque and Van Rossem 2015;Missinne and Bracke 2012;Schrier et al 2012). This higher incidence of health problems is particularly worrisome when considering the negative impact of health problems on employment.…”
Section: Introductionmentioning
confidence: 99%